(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
In this comprehensive exploration, we navigate diverse perspectives on word meaning, encompassing semantic theory, syntactic approaches, pragmatics, cognitive semantics, linguistic relativity, and lexical semantics. Each approach sheds light on different facets of how we derive and interpret meaning in language. The semantic theory emphasizes the link between words and real-world entities, reflecting the foundational principles of dictionaries. Syntactic approaches delve into the grammatical structures that influence meaning, with Chomsky’s generative grammar highlighting the role of sentence structure. Pragmatics introduces context and social factors as integral components, recognizing the dynamic nature of meaning in communication. Cognitive semantics takes us into the realm of mental processes, exploring how our minds construct meaning. The linguistic relativity hypothesis challenges us to consider how language shapes our perceptions and cognitive processes. Lexical semantics zooms in on the intricate relationships between individual words, providing a detailed map of word meanings through tools like thesauruses and semantic networks. Furthermore, we expand our perspective by considering the evolutionary lens, where language and meaning are seen as adaptive traits that have played a crucial role in human survival and cooperation. This interdisciplinary approach adds a layer of complexity, integrating insights from linguistics, cognitive science, and evolutionary psychology. This annotation serves as a guide through the rich tapestry of approaches to word meaning, highlighting the interconnectedness of linguistic, cognitive, social, and evolutionary dimensions in our quest to unravel the intricacies of language and communication.